Role of pin profile on material flow during friction stir welding of nylon-6 - Zafar, A. (Asian Research Publishing Network, 2016)
In friction stir welding, pin profile of the tool has a strong influence on weld quality due to its key-role in material flow. Its influence has been investigated on nylon-6 plates using three different pin profiles; threaded, square and tapered. Marker material insert technique was utilized for visual analysis of material flow of post-weld specimens. Results have shown uniform vertical stirring with symmetrical pattern for all pins either marker material is on advancing side or retreating side. Unlike metals, major role of pin profile was found in horizontal displacement in which square pin showed largest backward displacement of marker material. Moreover, no forward flow on any side (advancing or retreating side) of all pin profile was found. Â© 2006-2016 Asian Research Publishing Network (ARPN).